Successful Coronary Stent Retrieval from the Saphenous Vein Graft to Right Coronary Artery - Mustafa Aydin; Muhammet Rasit Sayin (Case Reports in Medicine)
Stent dislodgement and migration is a rare but serious complication of stent usage. For extraction of unexpanded stents different techniques have been described previously. We describe a case which used small baloon catheter for retrieval of a stent from the SVG-RCA.